2014
DOI: 10.4103/1319-2442.124577
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of public attitude toward living organ donation in Kano, northern Nigeria

Abstract: Organ shortage is a major public health challenge for transplant programs globally. The sustenance of such programs as an effective therapy for end-stage organ failure (ESOF) requires an exploration of public awareness and willingness to donate organs. This is imperative, especially in developing countries where ESOF is highly prevalent. We studied the awareness and predictors of public attitude toward organ donation in Kano city in northern Nigeria. Using interviewer-administered questionnaires, we assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
8
23
1
2
Order By: Relevance
“…The most common source of information on kidney donation in both KCC and BUTH was through television which agreed with findings from some previous studies (18,19). This was different from electronic media that was reported to be the most common source of awareness on kidney donation in Northern Nigeria (17).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most common source of information on kidney donation in both KCC and BUTH was through television which agreed with findings from some previous studies (18,19). This was different from electronic media that was reported to be the most common source of awareness on kidney donation in Northern Nigeria (17).…”
Section: Discussionsupporting
confidence: 87%
“…Also, the majority of the respondents from BUTH had a higher social class compared to their KCC counterparts which may also explain their better knowledge. Iliayasu et al reported that 79.6% of respondents in Northern Nigeria had good knowledge of kidney donation which is higher than the finding in our study (17). Also, good knowledge of organ donation was reported in 60% of respondents by Odusanya et al while Alam reported 63.9% in Saudi Arabia which is similar to the present study (16,18).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies showed that a high rate of education and knowledge concerning transplantation and donation of organs are seen as significant positive factors towards this issue (18, 19). Even though previous studies considered that knowledge and willingness do not increase interest in donation dramatically (20), knowledge could be an importance factor to improve the positive attitude toward organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated knowledge and attitude towards OD from various countries but there are few reports from the Middle East area and especially Egypt [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Egypt is an Arab country with a Muslim majority in its population.…”
Section: Introductionmentioning
confidence: 99%